DINAMIKA KECEMBURUAN SOSIAL DI MASYARAKAT NON-PENERIMA PKH: TINJAUAN TERHADAP IMPLEMENTASI KEBIJAKAN REJE DI KAMPUNG MERAH MEGE - Ismawati Saragih; Ahmad Sobirin (Cross-border, 2022)
At this time, there is often social jealousy caused by the provision of social assistance by the government, people who have never felt the touch of their help feel jealous, and this is the phenomenon that is happening now. Therefore, there needs to be action from a Reje (Village Head) to make policies in dealing with social jealousy that often occurs today. This is what researchers want to know about Reje's policy in dealing with social jealousy of non-PKH beneficiaries and how Reje's challenges and opportunities are in dealing with social jealousy of non-PKH beneficiaries in Kampung Merah Mege. This research uses a qualitative approach where the main data sources are the Red Village Mege Apparatus, Non-PKH beneficiary families, PKH Companions. Data collection techniques in this study used interviews, observation and documentation. The data analysis process starts from reviewing all interview data and documentation studies followed by conducting data reduction, presenting data into data verification tables to draw conclusions. The results of this study show that Reje's policy in dealing with social jealousy is by socializing PKH programs, providing BLT DD assistance, food security programs for non-PKH beneficiaries. Related to the challenges faced by Reje in dealing with this Reje policy are dissatisfaction and a sense of injustice and conflict and violence. Regarding the opportunities of the reje policy, namely the implementation of a transparent system and the return of mutual cooperation.